Effect of Taurine on the antimicrobial efficiency of Gentamicin - Islambulchilar Mina (Advanced Pharmaceutical Bulletin, 2011)
Context: Gentamicin is mainly used in severe infections caused by gram-negatives. However toxicity including nephrotoxicity and ototoxicity is one of the most important complications of its treatment. The production of free radicals seems to be involved in gentamicin toxicity mechanism. Taurine, a major intracellular free β-amino acid, is known to be an endogenous antioxidant. So potentially the co-therapy of taurine and gentamicin would reduce the adverse effects of the antibiotic. Objectives: In this study, we wished to know the effect of taurine on the antibiotic capacity of gentamicin. methods: strains of P. aeruginosa, E. coli, S. aureus and S. epidermidis were used as test organisms. Minimum inhibitory concentrations of gentamicin in the presence and absence of taurine at quantities from 40 to 2 mg/L were determined using macro-dilution method. Results: MICs were determined in the various concentrations of taurine for bacterial indicators. The MIC values of gentamicin for P. aeruginosa, S. aureus and E. coli remained unchanged in the values of 2.5, 5 and 20 μg/ml respectively in the absence and presences of different concentrations of taurine. The bactericidal activity of gentamicin against S. epidermidis was increased by addition of taurine in the concentrations higher than 6 mg/L. Conclusion: According to our study the antibacterial activity of gentamicin against the indicator microorganisms were not interfere with taurine at selected concentrations. Further in vivo studies are needed to establish if a combination of gentamicin and taurine would have the same effect.